2017
DOI: 10.1590/1807-7692bar2017160110
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Decline Research Review: Challenges and Issues for a Future Research Agenda

Abstract: Organizational decline is related to the deterioration of the resource base and performance of an organization for a sustained period of time. Although some studies have been conducted, it remains an understudied phenomenon, despite its importance. The study of organizational decline is faced with challenges to improving and increasing research. In this study, we analyze the scientific field of organizational decline in business and management journals with a high impact factor. We conducted a mixed-method stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 100 publications
0
22
0
11
Order By: Relevance
“…In this sense, our study makes an explicit link between strategy and bankruptcy (Daily, 1994;Sheppard, 1994;Trahms et al, 2013). More specifically, the reorganization plan is important because it brings empirical evidence on two research gaps, namely: the turnaround strategies that goes beyond retrenchment (Schweizer & Nienhaus, 2017) and the strategic decision process and practice under organizational decline (Serra et al, 2017). The examination of reorganization plans, moreover, is in line with recent studies that use documentary, qualitative evidence in the context of corporate decline (Muñoz-Izquierdo, Segovia-Vargas, Camacho-Miñano, & Pascual-Ezama, 2019).…”
Section: Open Accessmentioning
confidence: 76%
See 2 more Smart Citations
“…In this sense, our study makes an explicit link between strategy and bankruptcy (Daily, 1994;Sheppard, 1994;Trahms et al, 2013). More specifically, the reorganization plan is important because it brings empirical evidence on two research gaps, namely: the turnaround strategies that goes beyond retrenchment (Schweizer & Nienhaus, 2017) and the strategic decision process and practice under organizational decline (Serra et al, 2017). The examination of reorganization plans, moreover, is in line with recent studies that use documentary, qualitative evidence in the context of corporate decline (Muñoz-Izquierdo, Segovia-Vargas, Camacho-Miñano, & Pascual-Ezama, 2019).…”
Section: Open Accessmentioning
confidence: 76%
“…That is to say, the reorganization plan plays a role in the process of business recovery. Although the literature on turnaround is extensive, we consider that an analysis of the reorganization plans can bring new insights into the turnaround strategies used by companies (Schweizer & Nienhaus, 2017) and the decision process and practice in times of organizational decline (Serra et al, 2017). Our study is a step in this direction, showing how the strategic components of reorganization plans relate to firm performance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Serra et al (2017) studied the extant literature on the theory of organizational decline and turnaround and found that management researchers have used multiple theoretical lenses to study the said phenomenon. The study classified the academic literature into three broad categories, that is, organizational decline, turnaround and mortality.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…To understand and analyze problem choice, we selected the literature on 'organizational decline' as a relevant research topic (see, for instance, Collins, 2009;Damodaran, 2011;Hamel, 2012;McMillan & Overall, 2017;Whetten, 1980). This goes somewhat against the grain of mainstream research on growth that is prevalent in business and management journals (Serra, Pinto, Guerrazzi, & Ferreira, 2017). Despite the pervasiveness of organizational decline in countries, the extant research has not succeeded in explaining firms' failures (Garicano & Rayo, 2016).…”
Section: Introductionmentioning
confidence: 99%